Questioning in political debates: how citizens manage to speak in public - Schepen, Nynke van (2019)
Abstract: Adopting the methodological framework of Conversation Analysis and Interactional Linguistics, this dissertation explores how a particular interactional format, French yes/no interrogatives, is adopted by citizens in participatory meetings with politicians and experts to format and accomplish actions that are not only traditionally associated with asking questions or questioning, but also actions such as criticising and blaming. Special attention is paid to the formulation of the complex turns produced by the citizens and the responses that their recipients provide to the actions carried out. As a result, this dissertation demonstrates that even though questions are an ordinary type of action in everyday conversation, they constitute a specialised type of action within some institutional contexts, such as political meetings. In the meetings studied, they represent a powerful way for citizens not only to seek information, but also to display a political opinion and express critical positions. Question–answer sequences therefore become a window into larger issues related to transparency, entitlement and rights and obligations, as well as bring participatory democracy into being